PANDANGAN HUKUM POSITIF DAN HUKUM PIDANA ISLAM MENGENAI PENGANIAYAAN HEWAN: STUDI KASUS PENGANIAYAAN ANJING DI KABUPATEN ACEH SINGKIL PEMBUKAAN WISATA HALAL - Salsabilah, Eva Nurhafiah; Huda Maheswara, Moh. Yuflih (UI Scholars Hub, 2021)
One of the essential sectors that drive the national economy is the tourism sector. Nowadays, the halal tourism sector (halal tourism) is starting to be developed in various countries. In Indonesia, the government coordinates with various parties for the realization of halal tourism which is starting to develop in various regions, including Aceh. One of the events that attracted attention related to halal tourism was the case of persecution of dogs by the apparatus in Aceh Singkil Regency. The rise of this news prompted the local government to form an investigative unit to investigate the alleged abuse of the animal. As for this article, we will discuss the Positive Legal Views and Islamic Criminal Law regarding Animal Abuse for the sake of opening halal tourism in Aceh Singkil Regency. Halal tourism is a tourist visit activity that is managed by fulfilling Islamic sharia. Indeed, in reality, dogs are one of the forbidden animals, but acts of abuse or violence against these animals, especially for halal tourism purposes, are not justified. This is because the act of animal abuse is prohibited in Positive law and also in Islamic Criminal Law. Positive law itself regulates animal abuse in Article 302 of the Criminal Code and other laws and regulations with criminal threats. Whereas in Islamic criminal law itself, animal abuse is an act that is prohibited but is not regulated regarding the punishment, so that this act of animal abuse is classified as a ta'zir finger. The research method used in this paper is a normative legal research method supported by literature study analysis techniques.